Revisiting gender differences: What we know and what lies ahead - Meyers‐Levy, Joan; Loken, Barbara (Journal of Consumer Psychology, 2015)
Abstract Efforts to identify and understand gender differences have a long history that has sparked lively debate and generated much public interest. Although understanding gender differences is pivotal to consumer researchers and marketers, investigations into this issue by such individuals have been few in number, often weak in theory, and rather limited in progress made. This paper strives to reinvigorate such inquiry. We begin by describing four major theories of gender differences (socio‐cultural, evolutionary, hormone‐brain, and the selectivity hypothesis) and then assess relevant research from 2000 to 2013 in marketing, psychology, and biomedicine. From this, five conclusions emerge: Males are more self‐oriented, while females are more other‐oriented; females are more cautious responders; females are more responsive to negative data; males process data more selectively and females more comprehensively; and females are more sensitive to differentiating conditions and factors. We conclude by identifying several areas of opportunity for advancing our understanding of gender differences.